A Copula‐Based Non‐parametric Measure of Regression Dependence. (20th February 2012) - DETTE, HOLGER; SIBURG, KARL F.; STOIMENOV, PAVEL A.
<x xml:space="preserve">Abstract</x> Abstract. This article presents a framework for comparing bivariate distributions according to their degree of regression dependence. We introduce the general concept of a regression dependence order (RDO). In addition, we define a new non‐parametric measure of regression dependence and study its properties. Besides being monotone in the new RDOs, the measure takes on its extreme values precisely at independence and almost sure functional dependence, respectively. A consistent non‐parametric estimator of the new measure is constructed and its asymptotic properties are investigated. Finally, the finite sample properties of the estimate are studied by means of a small simulation study.